2010
DOI: 10.1080/15401383.2010.527785
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Perceived Mutuality in Women: Further Validation of the Connection–Disconnection Scale

Abstract: Relationships with family and significant friends and partners are important contributors to the quality of life, health, and mental health of women. The Connection-Disconnection Scale (CDS) was developed to assess perceived mutuality (PM) in relationships with mothers, fathers, friends, and romantic partners, and data are presented here that offer additional reliability and validity for the scale with college women. Two samples totaling 152 women from a midwestern university completed the CDS along with theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Internal consistency estimates for the CDS are excellent for college women, with Cronbach's alphas for the four versions (mother, father, friend, partner) at .96 and above (Sanftner & Tantillo, 2009). Test-retest estimates range from .67 (friend) to .91 (mother) (father = .85; partner = .71) (Sanftner & Tantillo, 2009).…”
Section: Methodsmentioning
confidence: 91%
“…Internal consistency estimates for the CDS are excellent for college women, with Cronbach's alphas for the four versions (mother, father, friend, partner) at .96 and above (Sanftner & Tantillo, 2009). Test-retest estimates range from .67 (friend) to .91 (mother) (father = .85; partner = .71) (Sanftner & Tantillo, 2009).…”
Section: Methodsmentioning
confidence: 91%
“…Finally, results from a program evaluation of an 8-week outpatient Multifamily Therapy Group based on an integrated Relational-Motivational approach showed improvements in perceived mutuality with fathers and mothers, as well as ED symptom improvements between pre-and post-group assessments, including reduced EDE-Q4 Restraint and EDI-3 DT, BD, and BU (Tantillo, 2010(Tantillo, , 2011). …”
Section: Advances In Eating Disorders: Theory Research and Practicementioning
confidence: 96%
“…Findings have shown that perceived mutuality is a good measure of how well people in a relationship (including those without psychiatric illness and women with ED) are able to mutually engage in the identification and repair of interpersonal disconnections (Genero et al, 1992;Jordan, 2010;Sanftner & Tantillo, 2010;Sanftner, Tantillo, & Seidlitz, 2004;Tantillo & Sanftner, 2010a). They have also shown a link between perceived mutuality and ED symptoms.…”
mentioning
confidence: 91%
See 2 more Smart Citations